Evolving indications and long-term oncological outcomes of risk-reducing bilateral nipple-sparing mastectomy. Issue 2 (26th November 2018) - Grobmyer, S R; Pederson, H J; Valente, S A; Al-Hilli, Z; Radford, D; Djohan, R; Yetman, R; Eng, C; Crowe, J P
Abstract: Background: Bilateral nipple-sparing mastectomy (NSM) is a technically feasible operation and is associated with excellent cosmetic outcomes. The aim of this study was to evaluate trends in patient characteristics, indications for surgery and long-term outcomes of bilateral NSM for breast cancer risk reduction over time. Methods: A review of a single-centre experience with bilateral NSM performed between 2001 and 2017 for breast cancer risk reduction in patients without breast cancer was performed. Trends in patient characteristics and indications for surgery were evaluated over four time intervals: 2001–2005, 2006–2009, 2010–2013 and 2014–2017. Statistical analysis was performed using χ 2 tests. Results: Over the study period, 272 NSMs were performed in 136 patients; their median age was 41 years. The number of bilateral NSMs performed increased over time. The most common indication was a mutation in breast cancer-associated genes (104 patients, 76·5 per cent), which included BRCA1 (62 patients), BRCA2 (35), PTEN (2), TP53 (3) and ATM (2). Other indications were family history of breast cancer (19 patients, 14·0 per cent), lobular carcinoma in situ (10, 7·4 per cent) and a history of mantle irradiation (3, 2·2 per cent). The proportion of patients having a bilateral NSM for mutation in a breast cancer-associated gene increased over time (2001–2005: 2 of 12; 2006–2009: 9 of 17; 2010–2013: 34 of 41; 2014–2017: 61 of 66; P < 0·001). Mean follow-up was 53 months; no breast cancers were found during follow-up. Conclusion: The use of bilateral NSM for breast cancer risk reduction is increasing and the indications have evolved over the past 16 years. These excellent long-term oncological results suggest that bilateral NSM is a good option for surgical breast cancer risk reduction. Graphical Abstract: The indications for risk-reducing bilateral nipple-sparing mastectomy (NSM) have evolved over time. Bilateral NSM is a safe option for selected patients with increased breast cancer risk due to a mutation in a highly penetrant breast cancer gene, strong family history or prior exposure to chest wall irradiation. Further options in risk-reducing surgery